Work-Related Symptom and Injuries Among Vehicle Maintenance Worker: an Overview - Abdullah, Shukriah; Md Deros, Baba; A. Ghani, Jaharah; Kamaliana Khamis, Nor; ., . (International Journal of Engineering and Technology, 2018)
Vehicle Maintenance workers involve a task that is performed infrequently and exceptional conditions mainly to inspect, maintain and repair. The overview looks at past research on vehicle maintenance worker associate injuries and symptoms that influence their health and work. The purpose of this paper is to illustrate the issues, gather information and statistics on type of injuries, illness or symptoms arise from maintenance vehicle work to provide an effective way of understanding its nature of work. Methods search of the scientific database and the internet using the following keyword; ‘Vehicle maintenance worker’, ‘mechanic workers’, with injuries, incident and disease. Further point out other risk factors that influence work-related symptom and injuries, the program suggested, ergonomic implementation as a further approach to solving the rising issues with regards to maintenance vehicle sector. This paper administers a good understanding of car maintenance and its work task. By this knowledge, more flexible approach and efficient prevention can be done as a platform in tackling down work-related disease and injuries.